The impact of trauma debriefing on debriefers in the context of the South African Police Service (SAPS) Helping Professions, Limpopo Province - Taute, Florinda M. (University of Pretoria, 2013)
Dissertation (MSD (EAP))--University of Pretoria, 2005.